2017
DOI: 10.1590/0001-3765201720170194
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Piper aduncum extracts on Anticarsia gemmatalis (Hübner) (Lepidoptera: Erebidae) and Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Piper aduncum found naturally in the Amazon and southeastern Brazil, is known for its secondary metabolites that have activity on insects. Anticarsia gemmatalis and Spodoptera frugiperda are among the major insect pests associated with agricultural production. This research evaluated the biological activity of hexane, ethyl acetate, and ethanol extracts of P. aduncum leaves on mortality and duration of larval and pupal periods, as well as weight, width, and length of A. gemmatalis and S. frugiperda pupae. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
2
8
0
2
Order By: Relevance
“…e observed efficacy of the synthetic insecticide is consistent with other reports, but overuse or misuse can lead to ecological backlashes such as resurgence and resistance [34,35]. Despite the efficacy of insecticides against FAW, their potential effects on nontarget organisms such as natural enemies could be inevitable [36,37].…”
Section: Efficacy Of Botanical Extract and Intercropping Systems Against Fawsupporting
confidence: 85%
See 1 more Smart Citation
“…e observed efficacy of the synthetic insecticide is consistent with other reports, but overuse or misuse can lead to ecological backlashes such as resurgence and resistance [34,35]. Despite the efficacy of insecticides against FAW, their potential effects on nontarget organisms such as natural enemies could be inevitable [36,37].…”
Section: Efficacy Of Botanical Extract and Intercropping Systems Against Fawsupporting
confidence: 85%
“…High levels of antifeedant secondary compounds were reported in plants in the Piperaceae family that deter herbivores [40]. Similarly, significantly high FAW mortality of 3.3-96.7% was reported due to hexane extracts of West African black pepper, which contain higher phenylpropanoid content that inhibited the functioning of cytochrome P450 [34]. e relatively low FAW severity and maize infestation observed for the beans intercropping systems support the hypothesis of this study and are likely due to the confusing olfactory and visual cues received from the companion beans plants that probably served as the push component that repelled FAW larvae away from the maize plants.…”
Section: Efficacy Of Botanical Extract and Intercropping Systems Against Fawmentioning
confidence: 99%
“…Phytol (diterpene) and safrole (phenylpropanoid) were identified in the hexane extract of all plants and, to a lesser extent, in the ethanolic extracts of three of the four plants studied. The extraction of these two components with solvents of different polarities was previously reported by Lucena et al [46].…”
Section: Discussionmentioning
confidence: 92%
“…Bullangpoti et al (2012) [49] reported that 12,000 mg/L of an ethanolic extract of the dehydrated leaves of M. azedarach were necessary to reach 100% mortality in the third instar larvae of S. frugiperda. Regarding the insecticidal activity of plants of the genus Piper, Lucena et al (2017) [46] reported mortality percentages of 31% in S. frugiperda larvae exposed to 15,000 mg/L of an ethanolic extract of dehydrated leaves of Piper aduncum L. (Piperaceae). Celis et al (2014) [35] reported mortality percentages of 80.3% in second instar larvae of S. frugiperda exposed to ethanolic extracts of Piper arboreum Aubl.…”
Section: Discussionmentioning
confidence: 99%
“…Com esse objetivo, várias pesquisas desenvolvidas nos últimos anos têm sido realizadas visando avaliar o efeito inseticida das espécies vegetais em inúmeros insetos-praga, dentre eles, podemos citar: Aedes aegypti L. (FERNANDEZ et al, 2020;TAN et al, 2019;FERREIRA et al, 2019), lagartas desfolhadoras, tais como: Anticarsia gemmatalis (Hübner), Spodoptera exigua (Hübner) (KHAN et al, 2017), Spodoptera frugiperda (J.E. Smith) (LUCENA et al, 2017;SOSA et al, 2019) Na maioria dos óleos, com 500 ppm foi obtido 100% de mortalidade em 48 horas, comprovando a ação inseticida das espécies estudadas.…”
Section: Compostos Secundários Como Princípios Ativosunclassified